Provider based billing in the United States: The effect on government reimbursement. (3rd April 2021) - Walker, Victoria; Lawani, Uyi; Coustasse, Alberto
ABSTRACT: Introduction: Provider-based status has been a Medicare payment designation established by the Social Security Act. It has allowed facilities to bill for physician services based on facility type. Medicare reimbursement has been based on whether services were rendered at a freestanding healthcare facility or a provider-based facility. Provider-Based Billing [PBB] comprises of two separate charges from the outpatient department, including a facility charge and a professional charge. Methodology: The methodology for this research analysis was a literature review complemented with a semi structure interview of a PBB expert. The review illustrated examples of provider-based clinics who have billed all Medicare patients as hospital outpatients that resulted in a charge for the Provider and the facility. Results: Results indicated that the reimbursement has been higher for hospitals that have implemented PBB. Discussion/ Conclusion: PBB has reported being the magnitude of increased Medicare and Medicaid reimbursements. It has required patients to pay higher copayments for office visits to cover the facility fee, but overall, the providers have received a higher payment. Innovation in the revenue cycle in hospitals and testing of new and more efficient procedures are essential and needed to change, adapt and survive in a new financial evolving financial environment.